Throughput and Delay Analysis of Interrupt-Driven Kernels under Poisson and Bursty Traffic - Salah, Khaled (2007)
This paper studies the performance of interrupt-driven kernels when subjected to heavy network traffic such as that of Gigabit Ethernet. Under heavy network traffic, the kernel performance will be negatively affected due to interrupt overhead caused by the incoming traffic. In particular, excessive latency and significant degradation in system throughput can be experienced. In this paper, we present analytical models to study the performance in terms of two key kernel performance metrics: throughput and delay. The performance is also studied using simulation. Both Poisson and bursty traffic with empirical packet size distribution are considered.